Levels of management and economic results of enterprises = Poziomy kierowania a rezultaty ekonomiczne przedsiębiorstw - Tokarski, Stefan; Tokarski, Krzysztof; Sikora, Joanna (Zielona Góra: Faculty of Economics and Management Press)
In order to achieve competitive results, the manager must master the skills necessary for subsequent levels of management. In the present study we have verified three hypotheses regarding the correlation between the level of control and efficiency, a form of ownership and influence on the managing level to direct and indirect subordinates. Two of the hypotheses gained the expected level of significance and the third was statistically insignificant.
Keywords: poziom kierowania; wywieranie wpływu; wskaźniki rentowności; podwładny bezpośredni; podwładny pośredni; levels of management; influence; profitability ratios; direct subordinate; indirect subordinate